Deep terrestrial indigenous microbial community dominated by Candidatus Frackibacter - Sian E. Ford; Greg F. Slater; Katja Engel; Oliver Warr; Garnet S. Lollar; Allyson Brady; Josh D. Neufeld; Barbara Sherwood Lollar (Communications Earth & Environment)
Abstract Characterizing deep subsurface microbial communities informs our understanding of Earth’s biogeochemistry as well as the search for life beyond the Earth. Here we characterized microbial communities within the Kidd Creek Observatory subsurface fracture water system with mean residence times of hundreds of millions to over one billion years. 16S rRNA analysis revealed that biosamplers well isolated from the mine environment were dominated by a putatively anaerobic and halophilic bacterial species from the Halobacteroidaceae family, Candidatus Frackibacter. Contrastingly, biosamplers and biofilms exposed to the mine environment contained aerobic Sphingomonas taxa. δ13C values of phospholipid fatty acids and putative functional predictions derived from 16S rRNA gene profiles, imply Candidatus Frackibacter may use carbon derived from ancient carbon-rich layers common in these systems. These results indicate that Candidatus Frackibacter is not unique to hydraulically fracked sedimentary basins but rather may be indigenous to a wide range of deep, saline groundwaters hosted in carbon-rich rocks.